Non spontaneous vaginal delivery was associated with lower probability of subsequent fertility. (May 2020) - Guo, Congcong; Ma, Wenmin; Fan, Dazhi; Ma, Yubo; Liu, Li
Highlights: Cesarean birth had a 9% lower probability of subsequent fertility. Instrumental vaginal birth had a 2% lower probability of subsequent fertility. After adjusting for confounding factors, cesarean birth had a 10% lower probability of subsequent fertility. Abstract: Objective: Previous systematic reviews have reported that cesarean birth is associated with reduced rate of subsequent fertility. However, other common mode of delivery was poorly understood. The aim of this study was to systematically investigate the subsequent fertility in patients having different modes of non-spontaneous vaginal delivery, if compared to normal vaginal delivery. Study Designs: Medline (via PubMed), Web of Science, Embase (via Dialog), CENTRAL (via Cochrane Library), ScienceDirect (via Elsevier) and ClinicalTrial.gov were searched up to October 2019, without language restrictions in this systematic review and meta-analysis. Articles assessing the mode of delivery and subsequent fertility were included. Quality assessment was evaluated using the nine-point Newcastle Ottawa Scale by two independent reviewers. Results: Twenty-one articles, including 4, 423, 544 women of reproductive age, were included. Results showed that women had a 9% (RR: 0.91 [95 %CI 0.88, 0.94]) lower probability of subsequent fertility in primary cesarean birth group, compared with spontaneous vaginal delivery. Further analysis discovered that a 13 % (0.87, [0.85, 0.90]) lower probability of subsequent fertility was observed in women delivered by emergency cesarean birth, a 14 % (0.86, [0.82, 0.91) lower probability by elective cesarean birth, a 39 % (0.61, [0.57, 0.66]) by maternal-requested cesarean birth, and a 2% (0.98, [0.97, 1.00]) by instrumental vaginal delivery. Conclusions: Non-spontaneous vaginal delivery may be associated with lower probability of subsequent fertility. Decision makers and obstetricians should be cautious when choosing the mode of delivery.